Gene-environment interactions and colorectal cancer risk: A case-control study on xenobiotic metabolizing enzyme polymorphisms in the Jammu& Kashmir, India population - Gowhar Rashid; Gulzar A. Bhat; Tahseen Bilal Rather; Kulsum Akhter; Ishrat Parveiz; Irfan Maqbool; Syed Nisar Ahmad; Malik Tariq Rasool; Farooq Ahmad Jan; Syed Mudassar (Advances in Biomarker Sciences and Technology)
Background: Cancer remains a significant global health concern, with colorectal cancer (CRC) showing a rising incidence, particularly among younger populations. Most CRC cases are linked to a complex interplay of genetic and environmental factors. The cytochrome P450 (CYP) superfamily, including enzymes like CYP2A13 and CYP2A6, plays a vital role in metabolizing environmental carcinogens such as polycyclic aromatic hydrocarbons (PAHs) and nitrosamines. Polymorphisms in these genes, alongside phase II glutathione-S-transferases (GSTs) involved in detoxification, can influence individual cancer risk. This study focuses on the association between these genetic polymorphisms and CRC risk in the Jammu & Kashmir, population, a region with high exposure to dietary and lifestyle-related carcinogens. Methodology: This hospital-based case-control study was conducted at the Sher-I-Kashmir Institute of Medical Sciences (SKIMS), Srinagar, J&K, India between March 2019 and March 2022. The study included 246 histopathologically confirmed colorectal cancer (CRC) cases, and an equal number of matched controls based on age (±5 years), gender, and place of residence. Blood samples were collected for DNA extraction, followed by genotyping of xenobiotic-metabolizing enzyme (XME) genes, including CYP2A13, CYP2A6, and GSTs using standard PCR-RFLP and multiplex PCR methods. Statistical analyses were performed using STATA software to assess the association between gene polymorphisms and CRC risk. Results: The study revealed key associations between genetic and environmental factors and CRC risk. The analysis demonstrated that cases had significantly lower education levels than controls. Family history of cancer, smoking, and dietary factors like red meat and salt tea consumption were more prevalent among cases. Genetic analysis identified significant interactions between various CYP and GST genotypes, and environmental factors such as smoking, pesticide exposure, and diet, with varying effects on CRC risk. Conclusion: The research underscores the influence of genetic and environmental factors on colorectal cancer (CRC) risk. Lower educational was associated with a heightened risk of CRC. Certain genotype variants of xenobiotic metabolizing enzymes (XME) were found to increase CRC risk, particularly in conjunction with smoking, pesticide exposure, and sun-dried vegetable consumption. A family history of cancer, especially CRC, further amplified the risk. These findings emphasize the importance of developing personalized CRC prevention and screening strategies that account for gene-environment interactions.